Reproducibility of a commercially available subgingival plaque sampling strategy and analysis strategy with oligonucleotide probes - Pretzl, Bernadette; Paul, Jule; Krigar, Diana-Maria; Uhlmann, Lorenz; Eickholz, Peter; Dannewitz, Bettina (Acta odontologica Scandinavica, 2017)
Objectives: The aim was to evaluate the intra-test agreement of pooled samples from the deepest periodontal pocket of each quadrant with a commercially available test kit based on hybridization of 16S rRNA.Material and methods: Plaque samples of 50 patients with generalized severe chronic periodontitis before therapy were pooled in two separate vials in order to detect and compare counts of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola. Cohen’s κ and interclass correlation coefficients were calculated to judge intra-test agreement.Results: Cohen’s κ for detection and counts of Tannerella forsythia and Treponema denticola showed a perfect agreement. Porphyromonas ginigivalis was identified in both tests with a substantial agreement, whereas detection of Aggregatibacter actinomycetemcomitans varied in eight patients resulting in a good agreement. Possible confounding factors could not be identified statistically.Conclusion: Test results of the commercial 16S rRNA test are perfectly reproducible regarding detection of red complex pathogens. Intra-test agreement concerning detection of Aggregatibacter actinomycetemcomitans was less favorable.Clinical relevance: Detection of certain periodontal pathogens may alter the treatment and lead to prescription of antibiotics parallel to mechanical debridement. It is quite important not to use antibiotics excessively. Thus, the basis for decision-making in favor of antibiotics should be solid.